Photoluminescence from Liquid-Exfoliated WS2 Monomers in Poly(Vinyl Alcohol) Polymer Composites - COLEMAN, JONATHAN; DUESBERG, GEORG (My University, 2016)
While liquid phase exfoliation can be used to produce nanosheets stabilized in polymer solutions, very little is known about the resultant nanosheet size, thickness or monolayer content. Here we use semi-quantitative spectroscopic metrics based on extinction, Raman and photoluminescence (PL) spectroscopy to investigate these parameters for WS2 nanosheets exfoliated in aqueous polyvinylalcohol (PVA) solutions. By measuring Raman and PL simultaneously, we can track the monolayer content via the PL/Raman intensity ratio while varying processing conditions. We find the monolayer population to be maximized for a stabilizing polymer concentration of 2 g/L. In addition, the monolayer content can be controlled via the centrifugation conditions, exceeding 5% by mass in some cases. These techniques have allowed us to track the ratio of PL/Raman in a droplet of polymer-stabilized WS2 nanosheets as the water evaporates during composite formation. We find no evidence of nanosheet aggregation under these conditions although the PL becomes dominated by trion emission as drying proceeds and the balance of doping from PVA/water changes. Finally, we have produced bulk PVA/WS2 composites by freeze drying where >50% of the monolayers remain unaggregated, even at WS2 volume fractions as high as 10%.
PUBLISHED
Cited By :5 Export Date: 15 September 2016
Keywords: nanosheets; nanosheets